A Rare Cause of Recurrent Vulvar Pain: Case Presentation of Periclitoral Abscess - Rengin Karataylı; Kazım Gezginç; Dilay Gök; Ali Acar (Medical Network, 2012)
Periclitoral abscess is a very rare disorder causing severe vulvar pain. There are only few cases that have been reported and the etiology is still unclear except some cases were found to be related to female circumcision in a group of patients. Periclitoral abscess can be recurrent and has also been seen in premenarchal girls. Antibiotic treatment and marsupialization are the treatment options. In this report, management of a case with recurrent periclitoral abscess is presented.